Changes in Upper Airway Volume in Edentulous Obstructive Sleep Apnea Patients Treated with Modified Mandibular Advancement Device. Issue 6 (30th September 2015) - Tripathi, Arvind; Gupta, Ashutosh; Sarkar, Sabyasachi; Tripathi, Suryakant; Gupta, Narendra
Abstract: Purpose: This study was an attempt to verify the utility of complete dentures modified as a mandibular advancement device (MAD) in effecting expansion in pharyngeal volume to treat obstructive sleep apnea (OSA) in edentulous patients. Materials and Methods: The sample consisted of 17 patients (12 male, 5 female, average age 61 ± 4 years; BMI, 22 ± 5; apnea hypopnea index [AHI] 15 to 30). All patients had worn complete dentures for at least 1 year; all patients had the dentures modified to a MAD. Five variables were assessed preoperatively and 6 months after wearing the modified MADs. These variables were: sleep efficiency, AHI, oxygen desaturation events/hr., mean oxygen saturation, snoring index, and airway volume. This assessment was done by subjecting the patients to all‐night polysomnography. Results: Without any prosthesis or device in the edentulous patients, the mean velopharyngeal volume was 8.05 ± 0.58 cm 3, oropharyngeal volume was 2.14 ± 0.38 cm 3, and hypopharyngeal volume was 3.26 ± 0.78 cm 3 . With complete dentures (unaltered) in the edentulous patients, the mean velopharyngeal, oropharyngeal, and hypopharyngeal volumes were 10.73 ± 0.98 cm 3, 2.60 ± 0.48 cm 3, and 4.31 ± 0.89 cm 3, respectively. There was a statistically significant change in the airway volume following insertion of the complete dentures modified as MADs with velopharyngeal, oropharyngeal, and hypopharyngeal volume recorded as 11.76 ± 1.07 cm 3, 3.33 ± 0.51 cm 3, and 4.94 ± 0.83 cm 3, respectively. Conclusion: From the results obtained in this limited small sample study, it was inferred that the pharyngeal expansion induced by complete dentures modified as MADs effectively reduced symptoms of OSA. Increased volume was most pronounced in the velopharynx region followed by hypopharynx and oropharynx.